Improving digital payment system services: The impact of e-service quality and e-Loyalty on user preferences - Soma, AM; Wati, Ina Kartika; Ispriyahadi, Heri (Universitas Negeri Surabaya, 2024)
This research aims to provide deeper insights into user preferences and the factors influencing their choices in using Digital Payment Systems, particularly in the context of the DANA e-wallet as an alternative to BI-Fast during service improvement periods. The study focuses on key variables such as E-System Quality and E-Loyalty. The findings indicate that the constructs of E-Loyalty and E-Service Quality demonstrate high levels of validity and reliability, and there exists a significant relationship between electronic service quality and electronic loyalty. Data analysis also identifies specific dimensions of DANA e-wallet service quality that have a significant impact on user preferences and loyalty levels. Factors such as compensation, ease of link access, and ease of contacting customer service are aspects that need attention to enhance service quality. Thus, the research conclusion provides valuable guidance for other Digital Payment Systems owners or managers to improve their service quality and strengthen customer relationships, akin to what is done by DANA e-wallet. These findings offer valuable guidance for other e-wallet owners or managers to enhance their service quality, focusing on aspects such as compensation, link access convenience, and ease of contacting customer service. The importance of improving electronic service quality to achieve higher customer loyalty should be emphasized by stakeholders in the digital payment industry, with specific steps that can be taken based on these findings to strengthen customer relationships and maintain competitive advantages.